Activities outside of the care setting for people with dementia: a systematic review. Issue 10 (6th October 2020) - D'Cunha, Nathan Martin; Isbel, Stephen; McKune, Andrew J; Kellett, Jane; Naumovski, Nenad
Abstract : Objectives: To summarise the evidence from interventions investigating the effects of out of care setting activities on people with dementia living in residential aged care. Design: A systematic review. Methods: A systematic search of electronic databases (PubMed, PsycINFO, Scopus, Web of Science and the Cochrane Library) was performed to identify intervention trials published from journal inception to January 2020. Controlled trials, or quasi-experimental trials, which measured pre-intervention, post-intervention or during-intervention outcomes, where the participants were required to leave the care setting to participate in an intervention, were eligible for inclusion. Quality appraisal of the studies was performed following the Cochrane Collaboration's Risk of Bias or Newcastle-Ottawa Scale tools. Results: Of the 4155 articles screened, 11 articles met the inclusion criteria from 9 different studies. The number of participants in the studies ranged from 6 to 70 people living with dementia and lasted for 3 weeks up to 5 months. The interventions were aquatic exercise, wheelchair cycling, art gallery discussion groups, an intergenerational mentorship programme, horse riding, walking and outdoor gardening. Overall, the studies indicated preliminary evidence of psychological (n=7), physical (n=4) and physiological (n=1) benefits, and all interventions were feasible to conduct away from the aged care facilities. However, the low number of participants in the included studies (n=177), the absence of a control group in all but three studies, and potential for selection bias, limits the generalisability of the findings. Conclusions: Activities outside of the residential aged care setting have the potential to be effective at providing a range of benefits for people living with dementia. Higher quality studies are required to encourage care providers to implement these type of activities in dementia care settings. PROSPERO registration number: CRD42020166518.